A székelyföldi és a felvidéki turisztikai szervezeti rendszer összehasonlító vizsgálata - Tőzsér Anett (Közép-európai Monográfiák, 2020)
The Hungarian-populated areas of the Carpathian Basin are many well-known or less known tourist destination areas, whose competitiveness is determined by the cooperation of the tourism actors. Therefore, the National Strategic Research Institute has launched a research series to provide a comprehensive picture of the functioning of these organizations. The first pilot project of this was the research of the tourism organization system of Szeklerland in the second half of 2015. Based on the methodological practice developed here, the area of the research was the Hungarian population of the Highlands in 2017. The aim of the research is to examine, on the basis of objective criteria, what Hungarian tourism destination management (TDM) type organizations exist and operate in the Hungarian areas of Szeklerland and the Highlands; to examine the conditions of the organizational operation, its legal and professional environment, the factors that help and hinder the operation and the most successful initiatives, as well as to explore the conditions of successful operation and, on the basis of these, to propose further possibilities, forms and operation of the tourism cooperation. The research was done with a qualitative method. The professional interviews of the six question blocks, consisting of forty questions, provided an opportunity to examine the topic in depth, to explore latent phenomena. With this method it was possible to gain a deeper understanding of the way of thinking, actions and attitudes of Hungarian organizations and professionals from Szeklerland and Upper Hungary. The results of the research and the recommendations formulated on the basis of this may contribute to the competitiveness of tourism in the rural areas of Szeklerland and Highlands due to the development of the organizational background, thus offering new economic opportunities for the local Hungarian communities, promoting their survival in the homeland, their economic strength. With the results of the research in the Szeklerland and the Highlands, and later planned in the other Hungarian regions of the Carpathian Basin, we prepare and strengthen the tourist co-operation.